Outcome of Pediatric Cataract Surgeries in a Tertiary Center in Switzerland - Sarah Claudia Ambroz; Marc Töteberg-Harms; James V. M. Hanson; Jens Funk; Daniel Barthelmes; Christina Gerth-Kahlert (Journal of Ophthalmology)
Purpose. To determine and to analyze the outcome of pediatric cataract surgery. Methods. A retrospective chart review of individuals aged up to 10 years who underwent cataract surgery between January 1, 2004, and December 31, 2014, at the UniversityHospital Zurich, Switzerland. Results. 63 children (94 affected eyes) with bilateral (68/94) or unilateral (26/94) cataract were identified. Surgery was performed at a median age of 1.5 months (IQR: 1.3–2.6 months) for the aphakic group (45/94) and of 50.7 months (IQR: 38.0–78.4 months) for the IOL group (49/94). At the last follow-up visit (median 31.1 months, IQR: 18.4–50.2 months), visual acuity was better in bilateral than in unilateral cataract cases. Posterior capsular opacification (PCO) was diagnosed in 30.9% of eyes without a significant difference in the IOL and aphakic groups (p=0.12). Aphakic glaucoma was diagnosed in 12/45 eyes at a median of 6.8 months (IQR 2.1–13.3 months) after surgery. Microcornea (5/12) and anterior segment anomalies (8/12) were associated with glaucoma development (p<0.05). Conclusion. Laterality and timing of surgery influence the outcome of pediatric cataract surgery. PCO was the most frequent postoperative complication. Aphakic glaucoma is often associated with ocular developmental abnormalities and a poor visual outcome.